Human papillomavirus and prostate cancer: The role of viral expressed proteins in the inhibition of anoikis and induction of metastasis. (March 2021) - Fatemipour, Maryam; Nahand, Javid Sadri; Fard Azar, Maryam Ebadi; Baghi, Hossein Bannazadeh; Taghizadieh, Mohammad; Sorayyayi, Saba; Hussen, Bashdar Mahmud; Mirzaei, Hamed; Moghoofei, Mohsen; Bokharaei-Salim, Farah
Abstract: Background: The aim of this study is to address the role of HPV in prostate cancer (PCa) development through the inducement of resistance to anoikis. Methods: In this case-control study, prostate tissues and blood samples were collected from 116 individuals, including 72 cases with PCa and 44 non‐malignant prostate tissue samples as a control group. The expression level of HPV genes (E2, E6, and E7) and cellular genes including anti-apoptotic mediators (Bcl-2 and survivin), tumor suppressor proteins (Rb and p53), and some mediators involved in anoikis resistance and invasiveness (E-cadherin, N-cadherin, Twist, PTPN13 and SLUG) were evaluated. Results: HPV genome was identified in 36.1% cases and 15.9% control samples, additionally there was found to be a statistic significant association between the presence of HPV and PCa (OR = 1.64, 95% C.I = 0.8–1.8, P-value = 0.023). HPV genotype 16 and 18 were the most prevalent genotype in both in the PCa group and the control group. The expression level of the tumor suppressor proteins (Rb and p53) and anti-apoptotic mediators (Bcl-2 and Survivin) were significantly decreased and increased, respectively, in the HPV-positive specimens compared to the HPV-negative specimens. Furthermore, the mean expression level of N-cadherin, SLUG, and TWIST in the HPV-positive specimens was higher than HPV-negative specimens while the mean expression level of PTPN-13 and E-cadherin genes in the HPV-positive specimens was lower than HPV-negative specimens. Conclusion: Our study suggests that HPV infection may be involved in the development of PCa metastases by modulating anoikis resistance related genes. Highlights: The expression level of the Rb and p53 were significantly decreased HPV-positive samples. The expression level of the Bcl-2 and Survivin were significantly increased in HPV-positive samples. Expression level of PTPN-13 and E-cadherin genes in the HPV-positive specimens was lower than HPV-negative samples. Expression level of N-cadherin, SLUG, and TWIST in the HPV-positive specimens was higher than HPV-negative samples.